A facile dissolution strategy facilitated by H2SO4 to fabricate a 2D metal-free g-C3N4/rGO heterojunction for efficient photocatalytic H2 production. (5th April 2018) - Wan, Jun; Pu, Chenchen; Wang, Ruimiao; Liu, Enzhou; Du, Xiao; Bai, Xue; Fan, Jun; Hu, Xiaoyun
Abstract: A 2D g-C3 N4 (pPCN)/rGO heterojunction for photocatalytic hydrogen production is fabricated by a facile dissolution strategy facilitated by H2 SO4 . The bulk g-C3 N4 (CN) can be directly exfoliated into ultrathin protonated g-C3 N4 (PCN) nanosheets under the assistance of H2 SO4, and PCN can be further modified by rGO in a dissolved state under the electrostatic self-assembly process. The nanocomposite exhibits a large surface area (146.47 m 2 /g) and intimate contact interfaces between pPCN and rGO due to the specific synthesis method. Based on the DRS, PL and photoelectrochemical analyses, the introduction of rGO can greatly improve the light absorption and photogenerated charge carrier separation and transfer of g-C3 N4 . The optimal pPCN/2 wt% rGO nanocomposite shows an efficient photocatalytic H2 evolution rate of 715 μmol g −1  h −1 under visible light irradiation, which is 2.6 and 13 times higher than those obtained on pPCN and CN. In addition, a photocatalytic mechanism over a 2D pPCN/rGO heterojunction is proposed. This work offers a new effective strategy for fascinating gC3 N4 based nanocomposites with promising hydrogen generation. Graphical abstract: Highlights: A dissolution strategy is developed for fabrication of 2D g-C3 N4 /rGO heterojunction. Bulk g-C3 N4 is directly exfoliated into ultrathin protonated g-C3 N4 nanosheet by H2 SO4 . g-C3 N4 /rGO nanocomposite exhibits enhanced photocatalytic H2 production performance. rGO can improve the light absorption and migration of photogenerated charge carriers.